Dual-biomarker-triggered fluorescence probes for differentiating cancer cells and revealing synergistic antioxidant effects under oxidative stress. Issue 7 (18th January 2019) - Zhang, Changyu; Zhang, Qiang-Zhe; Zhang, Kun; Li, Lu-Yuan; Pluth, Michael D.; Yi, Long; Xi, Zhen
Abstract : Dual-biomarker-triggered fluorescent probes were developed for simultaneous detection of the two biomarkers H2 S and hNQO1 in cancer cells. Abstract : Hydrogen sulfide (H2 S) and human NAD(P)H:quinine oxidoreductase 1 (hNQO1) are potential cancer biomarkers and also vital participants in cellular redox homeostasis. Simultaneous detection of these two biomarkers would benefit the diagnostic precision of related cancers and could also help to investigate their crosstalk in response to oxidative stress. Despite this importance, fluorescent probes that can be activated by the dual action of H2 S detection and hNQO1 activity have not been investigated. To this end, dual-biomarker-triggered fluorescent probes1 and2 were rationally constructed by installing two chemoselective triggering groups into one fluorophore. Probe1 provides a small turn-on fluorescence response toward H2 S but a much larger response to both H2 S and hNQO1 in tandem. By contrast, fluorescence probe2 is activated only in the presence of both H2 S and hNQO1. Probe2 exhibits a large fluorescence turn-on (>400 fold), high sensitivity, excellent selectivity as well as good biocompatibility, enabling the detection of both endogenous H2 S and hNQO1 activity in living cells. Bioimaging results indicated that probe2 could differentiate HT29 and HepG2 cancer cells from HCT116, FHC and HeLa cells owing to the existence of relatively high endogenous levels of both biomarkers. Expanded investigations using2 revealed that cells could generate more endogenous H2 S and hNQO1 upon exposure to exogenous hydrogen peroxide (H2 O2 ), implying the synergistic antioxidant effects under conditions of cellular oxidative stress.